Bioinspired Surface Layer for the Cathode Material of High‐Energy‐Density Sodium‐Ion Batteries. Issue 13 (22nd January 2018) - Jo, Chang‐Heum; Jo, Jae‐Hyeon; Yashiro, Hitoshi; Kim, Sun‐Jae; Sun, Yang‐Kook; Myung, Seung‐Taek
Abstract: Cathode materials are usually active in the range of 2–4.3 V, but the decomposition of the electrolytic salt above 4 V versus Na + /Na is common. Arguably, the greatest concern is the formation of HF after the reaction of the salts with water molecules, which are present as an impurity in the electrolyte. This HF ceaselessly attacks the active materials and gradually causes the failure of the electrode via electric isolation of the active materials. In this study, a bioinspired β‐NaCaPO4 nanolayer is reported on a P2‐type layered Na2/3 [Ni1/3 Mn2/3] O2 cathode material. The coating layers successfully scavenge HF and H2 O, and excellent capacity retention is achieved with the β‐NaCaPO4 ‐coated Na2/3 [Ni1/3 Mn2/3 ]O2 electrode. This retention is possible because a less acidic environment is produced in the Na cells during prolonged cycling. The intrinsic stability of the coating layer also assists in delaying the exothermic decomposition reaction of the desodiated electrodes. Formation and reaction mechanisms are suggested for the coating layers responsible for the excellent electrode performance. The suggested technology is promising for use with cathode materials in rechargeable sodium batteries to mitigate the effects of acidic conditions in Na cells. Abstract : A bio‐inspired β‐NaCaPO4 surface layer is applied to Na2/3 [Ni1/3 Mn2/3 ]O2, and the coated material dramatically improves the electrochemical and thermal properties. The β‐NaCaPO4 surface layer retards the particle separation and exfoliation which is the main cause of failure for long‐term cycling. The layer scavenges the generated HF, which would otherwise ceaselessly attack the active materials.